Пластичність еритроцитів і чинники серцево-судинного ризику у хворих на цукровий діабет 2-го типу - Приступюк, О. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
In patients with diabetes mellitus type 2 reduced deformability of red blood cells. Reduced deformability of red blood cells correlate with hyperglycemia, dyslipidemia, hypertension and excess of body weight. The state of the deformability of red blood cells is recommended as an integral component in the assessment of cardiovascular risk in patients with diabetes mellitus type 2.